1973
DOI: 10.1021/bi00728a024
|View full text |Cite
|
Sign up to set email alerts
|

Circular dichroic and immunologic studies of structure relations of insulin and derivatives

Abstract: Desoctapeptide-and desalanine-desasparagine insulins have similarly altered circular dichroic spectra compared to insulin. In contrast, the results of immunological studies clearly demonstrate significant conformational differences between these two types of structurally modified insulin molecules. Removal of alanine B-30 alone from insulin yields a derivative indistinguishable from insulin. It is concluded, therefore, that changes in structure of desalaninedesasparagine-insulin are due to the removal of Asn A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This arrangement results in the formation of a salt bridge between these two residues and favorably disposes the -NHof the A'' asparagine and the -COof the BZ3 glycine for hydrogen bond formation (Blundell et al, 1972). Data obtained from degradative and synthetic studies (Carpenter, 1966;Brugman & Arquilla, 1973;Arquilla & Stanford, 1972;Cosmatos el al., 1975Cosmatos el al., , 1976Blundell et al, 1972) strongly suggest that the A' ' asparagine, through the abovementioned interactions, is critically involved in the maintenance of a conformation of insulin compatible with high biological activity. In the [Arg"-A] insulin, however, the A21 arginine still retains the A' ' -B" salt bridge-and A' ' -BZ3 hydrogen bond-forming capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…This arrangement results in the formation of a salt bridge between these two residues and favorably disposes the -NHof the A'' asparagine and the -COof the BZ3 glycine for hydrogen bond formation (Blundell et al, 1972). Data obtained from degradative and synthetic studies (Carpenter, 1966;Brugman & Arquilla, 1973;Arquilla & Stanford, 1972;Cosmatos el al., 1975Cosmatos el al., , 1976Blundell et al, 1972) strongly suggest that the A' ' asparagine, through the abovementioned interactions, is critically involved in the maintenance of a conformation of insulin compatible with high biological activity. In the [Arg"-A] insulin, however, the A21 arginine still retains the A' ' -B" salt bridge-and A' ' -BZ3 hydrogen bond-forming capabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently only 1 or possibly 2 of the 28 hyperimmunized Lou/M rats were able to produce a humoral immune response to such cryptic epitopes. We have presented evidence for the presence of such cryptic epitopes (29).…”
Section: Discussionmentioning
confidence: 84%
“…Recent studies by A rquilla et al [1969], Brugman and Arquilla [1973], and others have indicated that the immunological specificity of the humoral response to insulin is directed to conformational sites on the intact molecule. Our results with the blastogénie test have shown that some patients' lymphocytes also respond to B chains, and, in rather fewer cases, to A chains.…”
Section: Discussionmentioning
confidence: 99%